In vitro evaluation of marginal leakage in bonded restorations, with mechanical or chemical-mechanical (Carisolv) removal of carious tissue - Okida, Ricardo Coelho [UNESP]; Martins, Thiago Marchi; Briso, André Luiz Fraga [UNESP] (FapUNIFESP (SciELO), 2007)
This study carried out an in vitro evaluation and comparison of the occurrence of marginal leakage in bonded restorations using mechanical or chemical-mechanical (Carisolv) removal of carious tissue. For that purpose, 40 extracted decayed human molars were divided into 4 groups: GI (burs + Prime & Bond NT + TPH), GII (Carisolv + Prime & Bond NT + TPH), GIII (burs + SBMP + Z100) and GIV (Carisolv + SBMP + Z100). After accomplishment of the restorations and thermal cycling, the teeth were exposed to dye, sectioned and qualitatively evaluated. The results demonstrated that the system of removal of carious tissue did not influence the results of microleakage at any of the cavity margins. At dentinal margins, use of the Prime & Bond NT + TPH restorative system allowed the occurrence of less microleakage than the SBMP + Z100 system.
Keywords: Dental caries; Dental leakage; Dental restoration; Permanent; Carisolv; glutamic acid; leucine; lysine; resin; tooth cement; unclassified drug; chemistry; comparative study; dental bonding; dental caries; dental surgery; endodontics; human; in vitro study; materials testing; methodology; standard; tooth disease; Composite Resins; Dental Bonding; Dental Caries; Dental Cavity Preparation; Dental Cements; Dental Leakage; Dental Restoration, Permanent; Glutamic Acid; Humans; Leucine; Lysine; Marginal Adaptation (Dentistry); Materials Testing